Jean Canavaggio, Cervantès dramaturge. Un thèâtre à naître. Presses Universitaires de France, Paris, 1977; 506 pp. - Joly, Monique (El Colegio de México, 1979)
Se reseñó el libro: Cervantès dramaturge. Un thèâtre à naître.